2023
DOI: 10.1007/s10787-023-01239-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of tirzepatide towards Covid-19 infection in diabetic patients: a perspective approach

Abstract: In Covid-19, variations in fasting blood glucose are considered a distinct risk element for a bad prognosis and outcome in Covid-19 patients. Tirazepatide (TZT), a dual glucagon-like peptide-1 (GLP-1)and glucose-dependent insulinotropic polypeptide (GIP) receptor agonist may be effective in managing Covid-19-induced hyperglycemia in diabetic and non-diabetic patients. The beneficial effect of TZT in T2DM and obesity is related to direct activation of GIP and GLP-1 receptors with subsequent improvement of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…It has been shown that GLP-1 and long-acting GLP-1 analogues are not only degraded by DPP4 but also by NEP. 82,83 NEP inhibition by specific inhibitors augments circulating GLP-1, which has a neuroprotective effect against Aβ-induced cytotoxicity, neuroinflammation, synaptic dysfunction-induced memory and cognitive dysfunctions. 82 Long 84 -acting GLP-1 analogues are highly resistant to the effect of DPP4.…”
Section: Nep Inhibitors and Glp-1mentioning
confidence: 99%
“…It has been shown that GLP-1 and long-acting GLP-1 analogues are not only degraded by DPP4 but also by NEP. 82,83 NEP inhibition by specific inhibitors augments circulating GLP-1, which has a neuroprotective effect against Aβ-induced cytotoxicity, neuroinflammation, synaptic dysfunction-induced memory and cognitive dysfunctions. 82 Long 84 -acting GLP-1 analogues are highly resistant to the effect of DPP4.…”
Section: Nep Inhibitors and Glp-1mentioning
confidence: 99%
“…Tirzepatide gastrointestinal adverse reactions mainly included nausea, vomiting, diarrhea, and decreased appetite, but the severity of these symptoms was mostly mild or moderate and the duration is relatively short. These effects are usually observed in irritable bowel syndrome and may suggest a potential effect of tirzepatide on the gut microbiota ( 40 ). The risk of hypoglycemia is significantly lower in the insulin group, slightly higher to the GLP-1 RA and placebo groups but without statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%